Pariwisata Berbasis Kearifan Lokal Minangkabau Dan Daya Saing Destinasi Kabupaten Solok Selatan - Siti Fatma; Eka Mariyanti (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2025)
The development of regional tourism faces increasing competition among destinations, which requires differentiation based on local uniqueness. South Solok Regency possesses strong Minangkabau cultural potential, reflected in its customary values, traditions, arts, and social systems. This study aims to analyze the role of Minangkabau local wisdom as a strategy to enhance the competitiveness of tourism destinations in South Solok Regency. The research employs a descriptive qualitative approach through literature review, field observations, and interviews with tourism stakeholders. The results indicate that the integration of Minangkabau local wisdom values, such as adat basandi syarak, syarak basandi Kitabullah, traditions of mutual cooperation, and local cultural practices, is able to create authentic tourism experiences and improve destination image. Furthermore, tourism based on local wisdom contributes to cultural preservation and the economic empowerment of local communities. Therefore, Minangkabau local wisdom has the potential to serve as a key strategy in enhancing the sustainable competitiveness of tourism destinations in South Solok Regency.